PENGARUH WORK-LIFE BALANCE, BEBAN KERJA, PAY SATISFACTION, DAN PSYCHOLOGICAL CAPITAL TERHADAP TURNOVER INTENTION PADA KARYAWAN KLINIK HEWAN X, TANGERANG [THE EFFECT OF WORK-LIFE BALANCE, WORKLOAD, PAY SATISFACTION, AND PSYCHOLOGICAL CAPITAL ON TURNOVER INTENTION OF EMPLOYEES AT X ANIMAL CLINIC, TANGERANG] - Hamdoyo, Audrey; Tjoa, Catrin; Bernarto, Innocentius; Graciella Jeanne Aretha Kurniawati; Ivonne Kristi (Universitas Pelita Harapan, 2024)
Veterinary clinic employees work under a demanding condition which may come from high expectation of recovery rate by clients and high risk of zoonotic disease exposure. An imbalance between the employee’s work life and personal life, high workload, disproportionate compensation, are all factors that can affect the physical and mental welfare of medical workers. Additionally, a low psychological capital plays an important role in mental health among vet clinic employees. One of the most common consequences of poor physical and mental well-being is the desire to leave (turnover intention). This study aims to determine the relationship between work-life balance (WLB), workload, pay satisfaction, and psychological capital (PsyCap) on turnover intention, as well as the correlation between these factors amongst employees at veterinary clinic X in Tangerang, Indonesia. This is a cross-sectional study with a sample size of 7 respondents. Using Kendall’s tau correlation method, the results show a significant correlation between components of work-life balance with components of pay satisfaction and psychological capital, as well as components of pay satisfaction with components of psychological capital and turnover intention. Dimension of WLB (PLIW) with pay structure (r=0,684; p=0,041); dimension of WLB (PLEW) with components of PsyCap: hope (r=0,651; p=0,046), resilience (r=0,651; p=0,046), optimism (r=0,769; p=0,020), and total PsyCap (r=0,651; p=0,046); component of pay satisfaction (benefit) with component of PsyCap, hope (r=0,651; p=0,046); component of pay satisfaction (pay structure) with indicator of turnover intention (r=-0,684; p=0,041). Abstrak Bahasa Indonesia: Karyawan klinik hewan bekerja dalam kondisi yang penuh tantangan karena ekspektasi kepulihan klien yang tinggi dan risiko tinggi dari paparan penyakit zoonosis. Ketidakseimbangan antara pekerjaan dan kehidupan pribadi, beban kerja yang berlebih, dan kompensasi upah yang tidak setara dengan beban kerja merupakan beberapa faktor yang dapat berdampak pada kesejahteraan fisik dan mental pekerja medis. Selain itu, Psychological capital yang rendah juga merupakan faktor psikis yang penting pada karyawan klinik hewan. Salah satu konsekuensi yang sering terjadi pada kondisi kesejahteraan fisik dan mental yang tidak tercukupi adalah keinginan untuk meninggalkan pekerjaan (turnover intention). Penelitian ini bertujuan untuk mengetahui hubungan antara work-life balance (WLB), beban kerja, pay satisfaction dan psychological capital (PsyCap) terhadap turnover intention, serta keterlibatan antar-faktor pada karyawan di klinik hewan X di Tangerang, Indonesia. Penelitian ini menggunakan desain cross-sectional, dengan jumlah sampel 7 responden. Menggunakan uji korelasi Kendall’s tau, ditemukan adanya hubungan yang bermakna antara dimensi WLB dengan komponen pay satisfaction dan psychological capital, serta komponen pay satisfaction dengan komponen psychological capital dan indikator turnover intention. Dimensi WLB (PLIW) dengan pay structure (r=0,684; p=0,041); dimensi WLB (PLEW) dengan komponen PsyCap: hope (r=0,651; p=0,046), resilience (r=0,651; p=0,046), optimism (r=0,769; p=0,020), dan PsyCap secara keseluruhan (r=0,651; p=0,046); komponen pay satisfaction (benefit) dengan komponen PsyCap hope (r=0,651; p=0,046); komponen pay satisfaction (pay structure) dengan indikator turnover intention (r=-0,684; p=0,041).